Parameter perturbations in a post-treatment chronic myeloid leukemia model capture the essence of pre-diagnosis A-bomb survivor mysteries - Radivoyevitch, Tomas (Radiat Environ Biophys, 2020)
A model of post-diagnosis chronic myeloid leukemia (CML) dynamics across treatment cessations is applied here to pre-diagnosis scenarios of A-bomb survivors. The main result is that perturbing two parameters of a two-state simplification of this model captures the essence of two A-bomb survivor mysteries: (1) in those exposed to > 1 Sv in Hiroshima, four of six female onsets arose as a cluster in 1969–1974, well after 5–10-year latencies expected and observed in two of six female- and nine of ten male cases (about one background case was expected in this high-dose cohort); and (2) no Nagasaki adult cases exposed to > 0.2 Sv were observed though about nine were expected (~ 1.5 background +  ~ 7.5 radiation-induced). Overall, it is concluded that: (1) whole-body radiation co-creates malignant and benign BCR-ABL clones; (2) benign clones are more likely to act as anti-CML vaccines in females than in males; (3) the Hong Kong flu of 1968 (and H3N2 seasonal flu thereafter) exhausted anti-CML immunity, thereby releasing radiation-induced clones latent in high-dose Hiroshima females; and (4) benign cells of 1–2 are CD4(+) as human T-cell leukemia-lymphoma virus-1 endemic to Nagasaki but not Hiroshima expands numbers of such cells. The next goal is to see if these conclusions can be substantiated using banked A-bomb survivor blood samples.